Environmental Degradation in India - Dimensions and Concerns: A Review - Saarangapani, B.; Sripathi, K. (Prabandhan: Indian Journal of Management, 2015)
This paper attempted to understand different dimensions of environmental degradation in India. The costs of environmental degradation were analyzed based on a recent report of the World Bank on the subject. Environmental sustainability could become the next major challenge for India as the costs of degradation are huge. The paper also threw light on different approaches to environmental degradation. Integrating sustainable development goals with the main stream of economic strategy have been suggested for preventing further degradation of the environment. Regulation of markets becomes imperative for preventing environmental degradation. It was argued that the current regulatory framework must be modified to cope with environmental pressures, irrespective of the origin of sources and for this, the regulatory capacity has to be increased with growing mandates of meeting sustainable development requirements.